A study on the effects of different factors influencing on customer loyalty, profitability and word of mouth advertisement for gaining competitive advantage in tourism industry - Naser Azad; Maryam Safaei; Mahdieh Shahrabi Farahani (Management Science Letters)
This paper presents an empirical investigation to study the effects of various factors influencing on customer loyalty, profitability and word of mouth advertisement for gaining competitive advantage in tourism industry. The study designs a questionnaire in Likert scale and distributes it among a random sample of 500 people who purchased some tours from travel agencies. Using structural equation modeling, the study has determined a positive and meaningful impact of pricing strategy, amenity, tourism services, content of trip, marketing mix elements, brand equity, competitive advantage and being exclusive on gaining competitive advantage. In addition, being exclusive and value creation influence positively on word of mouth advertisement. Finally, value creation influences on profitability, positively.